2016
DOI: 10.1038/gim.2015.196
|View full text |Cite
|
Sign up to set email alerts
|

Expanding noninvasive prenatal testing to include microdeletions and segmental aneuploidy: cause for concern?

Abstract: Yatsenko et al., 1 "Maternal Cell-Free DNA-Based Screening for Fetal Microdeletion and the Importance of Careful Diagnostic Follow-Up, " describing a single prenatal case identified by noninvasive prenatal screening as harboring a deletion at 22q11.2. Upon diagnostic postnatal testing, however, a smaller, noncritical deletion at 22q11.21 was identified. As stated by the authors, noninvasive prenatal screening (also referred to as noninvasive prenatal testing (NIPT)) has emerged as a powerful tool in screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 3 publications
4
14
0
Order By: Relevance
“…Similar to Case 1 here, their patient had a deletion downstream of the DiGeorge critical region that is present in <0.1% of the phenotypically normal population. A more recent report of a variety of non‐trisomic chromosomal anomalies reported by cfDNA has also described limited concordance with cytogenomic microarray . Here we report additional variants both in the 22q11 and 15q11 regions that suggest a general mechanism for false positive cfDNA testing.…”
supporting
confidence: 39%
“…Similar to Case 1 here, their patient had a deletion downstream of the DiGeorge critical region that is present in <0.1% of the phenotypically normal population. A more recent report of a variety of non‐trisomic chromosomal anomalies reported by cfDNA has also described limited concordance with cytogenomic microarray . Here we report additional variants both in the 22q11 and 15q11 regions that suggest a general mechanism for false positive cfDNA testing.…”
supporting
confidence: 39%
“…Sahoo et al followed up 19 cfDNA detected microdeletions (involving these 5 chromosomes) with diagnostic testing and found that only 5 could be confirmed with diagnostic testing. Most recently, Martin et al retrospectively analyzed the performance of SNP‐based NIPT in 80 449 fererrals for 22q11.2 deletion syndrome and 42 326 referrals for 1p36, cri‐du‐chat, Prader‐Willi, and Angelman microdeletion syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…For various microdeletions, testing laboratories have reported analytical validation using cell‐line or spike‐in samples and indicated very high sensitivities and specificities of >96% . However, the frequency of false negative results is essentially unknown in real‐world applications using commercial assays . In fact, to our knowledge, prior to this case, false negative results from similar commercial assays have not been reported.…”
Section: Casementioning
confidence: 93%